The Relationship Between the Use of Insecticide-Treated Mosquito Nets and Malaria Incidence in Gaura Village, West Lamboya District, West Sumba Regency - Sandewi, Aliefa Sansabila Putri; Koamesah, S. M. J.; Deo, Dwita A.; Tunggal, Deif (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Malaria remains a major public health problem in Indonesia, particularly in eastern regions such as East Nusa Tenggara. Gaura Village in West Lamboya District has the highest malaria incidence in West Sumba Regency. Insecticide-treated nets (ITNs) are a key prevention strategy, but their effectiveness depends on consistent use, net condition, and adequate household coverage. Objective to assess the relationship between ITN usage and malaria occurrence among residents of Gaura Village. Methods: This cross-sectional study included 252 participants. Data on malaria history, ITN use frequency, net condition, duration of use, washing frequency, and household coverage were collected through questionnaires and home observations. Statistical analyses included the Chi-square test and logistic regression. Results: Consistent ITN use was significantly associated with lower malaria incidence (p < 0.05). Net condition, bedroom coverage, and household member coverage also showed significant relationships with malaria occurrence. Multivariate analysis indicated that ITN usage remained the most influential variable. ITN usage is significantly associated with malaria incidence in Gaura Village. Ensuring consistent use, maintaining good net condition, and improving household coverage may strengthen malaria prevention efforts.